Interrogating the Traditional Methods of Crime Control of the Alago Ethnic Group - Ado Ahmad IBRAHIM (International Studies Journal)
This study investigates the Alago traditional methods of crime control. The analysis in the research is predicated on social control theory as the theoretical based. Data was gathered through secondary sources and interview. The study is a synthesis of previous study with the argument that the indigenous methods of crime control are viable for crime prevention in Alago society. The conclusion and recommendations are anchored on the findings discussed in the study.